Decreased peroxisome proliferator‐activated receptor γ level and signalling in sebaceous glands of patients with acne vulgaris. (1st July 2016) - Dozsa, A.; Mihaly, J.; Dezso, B.; Csizmadia, E.; Keresztessy, T.; Marko, L.; Rühl, R.; Remenyik, E.; Nagy, L.
Summary: Little is known about the altered lipid metabolism‐related transcriptional events occuring in sebaceous glands of patients with acne vulgaris. Peroxisome proliferator‐activated receptor (PPAR)γ, a lipid‐activated transcription factor, is implicated in differentiation and lipid metabolism of sebocytes. We have observed that PPARγ and its target genes, ADRP (adipose differentiation related protein) and PGAR (PPARγ angioprotein related protein) are expressed at lower levels in sebocytes from patients with acne than in those from healthy controls (HCs) Furthermore, endogenous PPARγ activator lipids such as arachidonic acid‐derived keto‐metabolites (e.g. 5KETE, 12KETE) are increased in acne‐involved and nonacne‐involved skin of patients with acne, compared with skin from healthy individuals. Our findings highlight the possible anti‐inflammatory role of endogenous ligand‐activated PPARγ signaling in human sebocyte biology, and suggest that modulating PPARγ‐ expression and thereby signaling might be a promising strategy for the clinical management of acne vulgaris.